Recreational Harvest of the Florida Bay Scallop: Hernando County - Brittany Hall-Scharf (EDIS, 2018)
This useful brochure written by Brittany Hall-Scharf and published by the UF/IFAS Florida Sea Grant College Program includes a full-color map identifying access routes to the boat ramps and marinas in Hernando County. Also find the latest information on scallops and scalloping, the recommended equipment you will want to bring, and a few tasty recipes for preparing Florida’s best summertime catch. https://edis.ifas.ufl.edu/sg148